2019
DOI: 10.1051/matecconf/201926601025
|View full text |Cite
|
Sign up to set email alerts
|

Key influencing factors for green public hospital building development in Malaysia

Abstract: The green hospital movement began years ago, following by several countries release their green rating system for the hospital buildings. In the past few years, a few newly constructed private hospital buildings in Malaysia have strived for the green building index certification. Paucity studies demonstrate that public hospital buildings have established for certifying the index. Despite the recognition of the importance of green building in achieving sustainability goal and the existence of many studies on is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…For instance, a study by Amran and Muhtazaruddin [20] found that implementing green building principles in hospitals can enhance patient welfare, assist curative processes, and utilize natural resources in an environmentally friendly manner. Additionally, Sahamir et al [21] discovered that green building implementation leads to significant measurable performance in energy and resource conservation, contributing to the realization of a green hospital. Furthermore, Marshal et al [22] established that the application of green building concepts in hospitals not only conserves energy but also reduces waste, thereby providing environmental benefits like improved air and water quality, waste reduction, and support for the conservation of natural resources.…”
Section: The Influence Of Green Building On Green Hospitalmentioning
confidence: 99%
“…For instance, a study by Amran and Muhtazaruddin [20] found that implementing green building principles in hospitals can enhance patient welfare, assist curative processes, and utilize natural resources in an environmentally friendly manner. Additionally, Sahamir et al [21] discovered that green building implementation leads to significant measurable performance in energy and resource conservation, contributing to the realization of a green hospital. Furthermore, Marshal et al [22] established that the application of green building concepts in hospitals not only conserves energy but also reduces waste, thereby providing environmental benefits like improved air and water quality, waste reduction, and support for the conservation of natural resources.…”
Section: The Influence Of Green Building On Green Hospitalmentioning
confidence: 99%
“…Commitment of all project participants 2 [45], [13] C3 Human resource CSF9 Skilled participants 6 [44], [45], [13], [50], [54], [55] CSF10 Experience in GBs 3 [44], [48], [50] C4 Management CSF11 Detailed plan 2 [45], [48] CSF12 Innovative management approaches 5 [44], [45], [13], [48], [54] CSF13 Support from senior management 3 [45], [13], [48] CSF14 Effective feedback and troubleshooting 3 [45], [13], [48] CSF15 High motivation 3 [45], [48], [55] CSF16 Integrated design 4 [46], [47], [57], [58] C5 Technology CSF17 Advanced machinery and equipment 4 [45], [13], [48], [54] CSF18 Available sustainable materials 5 [44], [47], [53], [54], [59] CSF19 Innovative technological approaches 7 [44], [45], [53], [54], [58]…”
Section: Csf8mentioning
confidence: 99%
“…tool. Control energy consumption and reduce energy loss have been identified as the major factor that contribute to the development of Green public hospital building [15]. Currently Hospital Langkawi is the first public hospital to achieved Gold level certification according to LEED green building certification tool.…”
Section: Fig 3 -Sustainability Program and Energy Performance Contramentioning
confidence: 99%